Evaluación de un intercambiador de calor para mejorar el proceso de calentamiento en el generador del sistema de refrigeración por absorción (2021)
The present work aims to solve one of the few problems that absorption refrigeration systems present, which consists of the relatively long times to reach a pseudo-stable state, for this we studied what happens when the conventional generator is replaced by an exchanger heat through a dynamic simulation using the NH3-H20 mixture as a working torque in the Aspen Plus® software, in order to study the time it takes for the generation temperature to stabilize. Taking a system with a cooling capacity of 3.50 kW studied by (Viswanathan et al., 2013), found that when the temperature of the heat transfer fluid changes 10 ° C, the generation temperature takes a little less than 6 minutes with a generator, while with power generation was found to take less tan immediately for the system to stabilize. In addition, other tests were carried out that showed that the thermal accumulation is almost null in the proposed system.